Synthesis, X-ray structures and magnetic properties of Ni(II) complexes of heteroaromatic hydrazone. (15th November 2020) - Keškić, Tanja; Jagličić, Zvonko; Pevec, Andrej; Čobeljić, Božidar; Radanović, Dušanka; Gruden, Maja; Turel, Iztok; Anđelković, Katarina; Brčeski, Ilija; Zlatar, Matija
Graphical abstract: Two binuclear double end-on azido bridged Ni(II) complexes, 1a and 1b, were synthesized and characterized by single-crystal X-ray diffraction. DFT benchmark for calculation of the exchange coupling J shows excellent performance of double-hybrid functionals. The calculated J for 1b agrees with experimentally determined J value. Highlights: Experimental and computational study of binuclear Ni(II) complexes. Single-crystal X-ray diffraction. Ferromagnetic coupling between double end-on azido bridged Ni(II) ions. DFT benchmark for calculation of the exchange coupling. EDA analysis of the role of crystal waters. Abstract: Two binuclear double end-on azido bridged Ni(II) complexes, [Ni2 L 2 ( μ -1, 1 -N3 )2 (N3 )2 ]⋅2H2 O (1a ), and [Ni2 L 2 ( μ -1, 1 -N3 )2 (N3 )2 ]⋅4H2 O (1b ) having the same inner sphere, where L =(( E )- N, N, N -trimethyl-2-oxo-2-(2-(1-(thiazol-2-yl)ethylidene)hydrazinyl)ethan-1-aminium, were synthesized from the same solution and characterized by single-crystal X-ray diffraction methods. Variable‐temperature magnetic susceptibility measurements showed intra-dimer ferromagnetic coupling between Ni(II) ions. The ferromagnetic coupling is supported by the broken-symmetry DFT calculations, with the level of theory chosen based on a benchmark study on 19 additional structurally related binuclear Ni(II) complexes. The role of water molecules in crystals of 1a and 1b is explained by DFT based energy decomposition analysis.